Six-Month Results From the Initial Randomized Study of the Ranger Paclitaxel-Coated Balloon in the Femoropopliteal Segment. (August 2017) - Bausback, Yvonne; Willfort-Ehringer, Andrea; Sievert, Horst; Geist, Volker; Lichtenberg, Michael; Del Giudice, Costantino; Sauguet, Antoine; Diaz-Cartelle, Juan; Marx, Claudia; Ströbel, Armin; Schult, Ingolf; Scheinert, Dierk; et al.
Purpose: To evaluate the performance of the Ranger paclitaxel-coated balloon vs uncoated balloon angioplasty for femoropopliteal lesions.Methods: Between January 2014 and October 2015, the prospective, randomized RANGER SFA study ( ClinicalTrials.gov identifier NCT02013193) enrolled 105 patients with symptomatic lower limb ischemia (Rutherford category 2–4) and stenotic lesions in the nonstented femoropopliteal segment at 10 European centers. Seventy-one patients (mean age 68±8 years; 53 men) were enrolled in the Ranger drug-coated balloon (DCB) arm and 34 patients (mean age 67±9 years; 23 men) were assigned to the control group. Six-month analysis included angiographic late lumen loss and safety and clinical outcomes assessments.Results: Baseline characteristics of the DCB and control groups were similar, as were lesion lengths (68±46 vs 60±48 mm; p=0.731), severity of calcification (p=0.236), and the prevalence of occlusions (34% vs 34%; p>0.999). At 6 months, late lumen loss was significantly less for the DCB group vs controls (–0.16±0.99 vs 0.76±1.4; p=0.002). The DCB group had significantly greater freedom from binary restenosis (92% vs 64%; p=0.005) and primary patency rates (87% vs 60%; p=0.014). Target lesion revascularization rates were 5.6% in the DCB group and 12% in the control group (p=0.475). No target limb amputations or device-related deaths occurred in either group.Conclusion: Six-month results suggest that Ranger DCB treatment effectively inhibited restenosis in symptomatic femoropopliteal disease, resulting in improved vessel patency and a low revascularization rate in the short term compared with uncoated balloon angioplasty.